Le film de genre est-il comparable à une "expérience de pensée" ? Révisions des concepts de déterminisme et d'agentivité dans trois films noirs (1947-1949) - El-Khoury, Toufic (Labyrinth, 2020)
Is genre film comparable to a thought experiment? Revising concepts of determinism and agency in three film noirs (1947-1949) The philosophical approach of film genres, first popularized by authors like Stanley Cavell, allows to consider genre films as narrative variations as pertinent to philosophical discourse as can be a traditional thought experiment, since every question on the essence of a genre (for example, what is a film noir?) and every discussion related to its inner functions, its mechanisms and its themes, generate naturally a philosophical discourse on the way a director uses filmic and narrative tools to transform his intentions into a specific system of meaning. This study adopts formalist and philosophical approaches to connect the narratives of the movies to the discourses it is prone to generate. The corpus draws on the ‘primitive scene' in three films noirs, Out of the Past (Tourneur, 1947), The Lady from Shanghai (Welles, 1947) et Criss Cross (Siodmak, 1949): the tragic meeting of an anti-hero with the woman who will be responsible of his fall. Indeed, the sequence showing this first meeting becomes an exercise in style where forerunning signs of the two protagonists' fall organize the writing and the mise-en-scene, and explicitly shows how questions of agency and determinism are intimately articulated to the narrative and formal frame of the movies.